Rapid thrombophilia genetic test facilitates improved prenatal care for mother and child - M.J. Kotze; C. la Grange; E.P.G. Mansvelt (South African Family Practice)
Physiological changes in coagulation factors during pregnancy are important to minimise blood loss during gestation and delivery, but may also lead to a 4–6 fold increased risk of venous thromboembolism during pregnancy and after delivery. Approximately 25% of maternal mortality can be ascribed to thromboembolism if untreated, while this figure is reduced to less than 1% when diagnosed on time. Clinical diagnosis is complicated by the fact that the symptoms associated with venous thrombosis are relatively common complaints of pregnant women. A rapid genetic test has been developed for simultaneous detection of the most common genetic risk factors associated with thrombophilia, the factor V 1691GA (Leiden) and prothrombin 20210GA mutations. Mutation 677CT in the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene, which increases homocysteine levels by 15–25% when two copies of the T-allele is present, is also included as part of this “prenatal care genetic test”. Hyperhomocysteinaemia has been associated with an increased risk of thrombosis and neural tube defects. The importance of multi-gene testing is emphasised by the low predictive value of any single inherited marker and the significant increase in the probability of thrombosis when more than one risk factor is identified.